Measurement of the Z boson production cross-section in pp collisions at √s = 5.02 TeV - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Glaser, Fabian; Günther, Paul André; et al. (Journal of high energy physics, 2024)
The first measurement of the Z boson production cross-section at centre-of-mass energy \sqrt{s} = 5.02 TeV in the forward region is reported, using pp collision data collected by the LHCb experiment in year 2017, corresponding to an integrated luminosity of 100 ± 2 pb−1. The production cross-section is measured for final-state muons in the pseudorapidity range 2.0 < η < 4.5 with transverse momentum pT > 20 GeV/c. The integrated cross-section is determined to beσZ→μ+μ−=39.6±0.7stat±0.6syst±0.8lumipb σ_{Z→ μ +μ -}=39.6± 0.7\left(stat\right)± 0.6\left(syst\right)± 0.8\left(lumi\right)pb
LHCb Collaboration: R. Aaij, S. Bachmann, D. Berninghoff, M. Borsato, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, G. Frau, F. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, J. Kubat, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, L. Promberger, M. Schmelling, R. Skuza, G. Tuci, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, M. Zavertyaev, Y. Zhao, A. Zhelezov [und 1066 weitere]
Gesehen am 22.10.2024